Management of Immune-Related Adverse Events in Patients With Non-Small Cell Lung Cancer - Burke, Michael; Rashdan, Sawsan (Frontiers in Oncology, 2021)
With the proven efficacy of the use of immunotherapy in almost all stages of lung cancer, immunotherapy toxicity has become a very important topic has that requires immediate recognition and management. The diagnosis of toxicities associated with immunotherapy can be very challenging and often requires multidisciplinary effort. This mini review gives an overview of the diagnosis and management of immune related adverse events that arise from using immunotherapy in lung cancer, potential biomarkers for early identification and future directions.